A model of endogenous financial inclusion: Implications for inequality and monetary policy - Mohammed Ait Lahcen; Pedro Gomis-Porqueras (University of Zurich, Department of Economics, 2018)
We propose a monetary dynamic general equilibrium model with endogenous credit market participation to study the impact of financial inclusion on welfare and inequality. We find that significant consumption inequality can result from limited access to basic financial services. In this environment, monetary policy has distributional consequences as agents face different liquidity constraints. This heterogeneity generates a pecuniary externality which can result in overconsumption of financially included agents above the socially efficient level. We conduct a quantitative assessment for the case of India. Our simple model is able to account for approximately a third of the observed consumption inequality. We analyze various policies aimed at increasing financial inclusion. As a result of pecuniary externalities, interest rate policies can result in a decrease in welfare and an increase in consumption inequality. Moreover, we find that a direct benefit transfer to bank account owners is superior to interest rate policies as it can increase welfare and reduce consumption inequality despite a decrease in individual consumption.
Keywords: E40; E50; 330; money; credit; banking; financial inclusion; inequality